The Implementation of Authority and Resolution Efforts Undertaken by the Ministry of Law and Human Rights (Kemenkumham) in Addressing the Case of Dualism within the Indonesian Notary Association (INI) - Yusuf Iman Yustiawan; Raden Roro Fara Anissa Putri (Journal of Private and Commercial Law, 2025)
This study aims to examine the implementation of the authority of the Ministry of Law and Human Rights (Kemenkumham) in conducting supervision and oversight to resolve the issue of dualism within the Indonesian Notary Association (INI) and the resolution efforts that can be undertaken to address this dualism. The issues raised in this study are: first, whether the Ministry of Law and Human Rights (Kemenkumham) exercised its authority to supervise and oversee the resolution of dualism within the Indonesian Notary Association (INI). Second, what resolution efforts can be undertaken by the Ministry of Law and Human Rights (Kemenkumham) regarding the dualism in the Indonesian Notary Association (INI). The research method employed is normative juridical, using a statutory approach. Data collection was conducted through a literature study. The findings indicate that the Ministry of Law and Human Rights (Kemenkumham), assisted by the Supervisory Council, has the authority to supervise and oversee the sole organization of notaries, INI, as stipulated in Article 82 of the Law on Notary Positions (UUJN) and as provided in Article 67 paragraphs (1) and (2) of the UUJN and Article 2 of the Ministerial Regulation on Law and Human Rights (Permenkumham). However, Kemenkumham lacks clear and definitive measures for conducting oversight and supervision to resolve the dualism issue. This is due to the absence of explicit regulations addressing dualism, whether in the UUJN, Permenkumham, or other regulations. As a result, Kemenkumham cannot fully exercise its authority in supervising and overseeing the dualism issue within the Indonesian Notary Association (INI). To resolve this issue, regulatory reform is necessary to enhance Kemenkumham’s authority in supervising and overseeing notary organizations, particularly in addressing the dualism within the Indonesian Notary Association (INI). The regulations requiring reform in this context include the UUJN and Permenkumham. Keywords: Indonesian Notary Association (INI), Ministry of Law and Human Rights, Authority, Resolution Abstrak Penelitian ini bertujuan untuk membahas mengenai bagaimana pelaksanaan kewenangan Kementerian Hukum dan Hak Asasi Manusia (Kemenkumham) dalam melakukan pembinaan dan pengawasan untuk menyelesaikan masalah dualisme Organisasi Ikatan Notaris Indonesia (INI) dan upaya penyelesaian yang dapat dilakukan untuk menangani permasalahan dualisme Organisasi Ikatan Notaris Indonesia (INI). Permasalahan yang diangkat dalam penelitian ini yaitu, Pertama, apakah dalam kasus dualisme Ikatan Notaris Indonesia (INI) Kementerian Hukum dan Hak Asasi Manusia (Kemenkumham) telah melaksanakan kewenangannya untuk melakukan pembinaan dan pengawasan dalam menyelesaikan kasus dualisme Ikatan Notaris Indonesia (INI). Kedua, bagaimana upaya penyelesaian yang dapat dilakukan oleh Kementerian Hukum dan Hak Asasi Manusia (Kemenkumham) terkait adanya dualisme dalam Ikatan Notaris Indonesia (INI). Metode penelitian yang digunakan ialah yuridis normatif dengan pendekatan perundang-undangan. Pengumpulan data melalui studi kepustakaan. Hasil kajian menunjukkan Kementerian Hukum dan HAM (Kemenkumham) yang dibantu Majelis Pengawas memiliki kewenangan untuk melakukan pengawasan dan pembinaan terhadap satu-satunya wadah tunggal Organisasi Notaris yaitu INI (Pasal 82 UUJN) sebagaimana telah tercantum dalam Pasal 67 ayat (1) dan ayat (2) UUJN dan Pasal 2 Permenkumham, akan tetapi Kemenkumham tidak memiliki langkah yang jelas dan pasti terkait bagaimana upaya pembinaan dan pengawasan yang harus dilakukan untuk dapat menyelesaikan dualisme tersebut. Hal ini disebabkan tidak adanya peraturan yang mengatur secara eksplisit untuk menyelesaikan permasalahan dualisme baik dalam UUJN, Permenkumham, maupun peraturan lainnya, sehingga Kemenkumham tidak dapat melaksanakan kewenangannya sepenuhnya dalam melakukan pembinaan dan pengawasan terhadap kasus dualisme dalam Ikatan Notaris Indonesia (INI). Untuk dapat menyelesaikan tersebut maka upaya penyelesaian yang diperlukan ialah dengan melakukan pembaharuan terhadap regulasi yang berkaitan dengan kewenangan Kemenkumham terhadap pembinaan dan pengawasan organisasi Notaris terutama dalam melakukan pembinaan dan pengawasan terhadap penyelesaian kasus dualisme Organisasi Ikatan Notaris Indonesia (INI), regulasi sebagaimana yang dimaksud dalam hal ini ialah UUJN dan Permenkumham. Kata Kunci: Ikatan Notaris Indonesia (INI), Kementerian Hukum dan Hak Asasi Manusia, Kewenangan, Penyelesaian